Developing a smartphone-based heads-up display (part 1) - Muhammad Zulhilmi Sazali (2019)
For decades, car automakers have been diligently researching on the improvement of the interior aesthetics of an automobile. As cars has been around for years, dated as far back to the 1940s, the dashboard, an interior panel of a car, has seen major improvements, both aesthetically and mechanically.